Prevalence of Function-Dependent Temporomandibular Joint and Masticatory Muscle Pain, and Predictors of Temporomandibular Disorders among Patients with Lyme Disease - Osiewicz, Magdalena (J Clin Med, 2019)
The aim was to determine the occurrence of temporomandibular disorders (TMDs) in patients with Lyme disease (LD), and to estimate the contribution of factors that may identify TMD among LD patients. In seventy-six (N = 76) adult patients with LD (mean age 57.6 ± 14.6 years) and 54 healthy non-Lyme volunteers with a mean age of 56.4 ± 13.5 years, possible function (i.e., non-pain) diagnoses were established using the Research Diagnostic Criteria of Temporomandibular Disorders (RDC/TMD). Pain diagnoses were established by means of the function-dependent dynamic and static tests. The two groups did not significantly differ in the frequency of disc displacements diagnoses and function-dependent pain diagnoses. LD showed a significantly higher frequency (p < 0.001) of osteoarthrosis than the control group. For the prediction of pain diagnoses in LD patients, the single regression analyses pointed out an association with age, sleep bruxism (SB), and awake bruxism (AB). Two predictors (i.e., SB (p = 0.002) and AB (p = 0.017)) were statistically significant in the final multiple variable model. The frequency of TMD in patients with LD based on function-dependent tests was not significantly different from that in the control group. This investigation suggests that the contribution of bruxism to the differentiation between patients with Lyme and TMD is high.